Pengintegrasian Aplikasi Shopee Untuk Mengoptimalkan Ekonomi Kreatif UMKM Desa Pakel Kabupaten Jombang Pada Revolusi Industri 4.0. - Sarah Putri Madania; Maulana Muhammad Daffa; Mu’tasim Billah; Ilham Nuril Fitri Huda; Aulia Nida’ul Husna; Bella Mega Riswanti; Mochammad Firmansyah (Jurnal of Management and Social Sciences, 2025)
Technology always experiences changes along with the times, changes in technology have a dynamic nature so that new innovations can emerge to create a technology that facilitates human activities in various sectors of activity such as industry, agriculture, education, and no less the economic sector which feels the impact of existing technological developments. The manifestation of these technological developments in the economic sector, namely e- commerce applications in the form of Shopee, the application of these applications during the industrial revolution 4.0 is expected to have an impact on society and especially UMKM actors to further develop a more creative economy so that they can open up employment opportunities as a whole for all levels and community elements, besides that the presence of the Shopee application can provide a new idea for the community so that they can be more independent and not depend on the government. Nowadays, everything is digital, both in cities and villages, in this case the presence of the Shopee application can be a new step for village governments to be able to take advantage of this application to take advantage of developing the economy in villages by developing the existing UMKM sector by utilizing technology. The existing one is the Shoppe application. In this case Pakel Village together with the East Java KKNT 09 UPN Veterans group created an account on the Shopee application to integrate UMKM products in Pakel Village, Jombang Regency. more widely known by the community both outside Pakel Village and outside the City of Jombang, so that UMKM in Pakel Village are ready to compete and develop in the industrial era 4.0.